1999
DOI: 10.1046/j.1365-2273.1999.00235.x
|View full text |Cite
|
Sign up to set email alerts
|

The anatomy of the lacrimal bone at the lateral wall of the nose: its significance to the lacrimal surgeon

Abstract: The position, dimension and thickness of the exposed lacrimal bone at the lateral nasal wall in 10 cadaveric half-heads were examined. In all cases, the lacrimal bone at the lateral nasal wall was found to be just anterior to the mid-third of the uncinate process. The average length and width was 7.4 mm and 2.5 mm, respectively. In nine of the 10 half-heads, the lacrimal bone was very thin with an average thickness of 57 mm. In all the cases, the position of the lacrimal passage covered by the lacrimal bone co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
2
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 3 publications
0
21
2
1
Order By: Relevance
“…Distances from the NLD opening, anterior nasal spine, maxillary sinus ostium, uncinate process, and other landmarks have been reported previously for assisting with localization of the lacrimal sac (Kim et al, 2012;Orhan et al, 2009;Tatlisumak et al, 2010;Yung and Logan, 1999). The maxillary line serves as a consistent anatomical landmark for endoscopic DCR surgery.…”
Section: Surgical Anatomymentioning
confidence: 94%
“…Distances from the NLD opening, anterior nasal spine, maxillary sinus ostium, uncinate process, and other landmarks have been reported previously for assisting with localization of the lacrimal sac (Kim et al, 2012;Orhan et al, 2009;Tatlisumak et al, 2010;Yung and Logan, 1999). The maxillary line serves as a consistent anatomical landmark for endoscopic DCR surgery.…”
Section: Surgical Anatomymentioning
confidence: 94%
“…In none of our cases the transillumination point was seen so anteriorly. Anatomical 14 and surgical 6 studies have suggested the unciform process as adjacent and posterior to the lachrymal fossa. Tsirbas and Wormald 19 stated that such structure must be preserved during DCR-en.…”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding, its endoscopic outline, without using palpation, is not so simple and even to palpate it with an instrument is difficult to distinguish the limits between the lachrymal bone and the unciform process, since they are adjacent structures of similar bone consistencies. Some authors 6,7,14 mention the identification of the lachrymal bone joint with the maxillary bone or with the unciform process as an intraoperative parameter. In our material the endoscopic outline of the lachrymal bone, the visualization of the maxillo-lachrymal junction, as well as the lachrymal bone joint with the unciform process was not possible.…”
Section: Discussionmentioning
confidence: 99%
“…The lacrimal bone is also situated just anterior to the middle third of the uncinate process, which has an average length and width of 7.2 and 2.5 mm, respectively [ 14 ].…”
Section: Lateral Nasal Wall Lacrimal Passagementioning
confidence: 99%
“…The lacrimal bone, which has a mean thickness of 0.057 [ 14 ] to 0.106 mm [ 15 ], is located posterior to the maxillary line. The lacrimal bone is also situated just anterior to the middle third of the uncinate process, which has an average length and width of 7.2 and 2.5 mm, respectively [ 14 ].…”
Section: Lateral Nasal Wall Lacrimal Passagementioning
confidence: 99%